What Can I Gift Myself? A Meeting between Christian and Buddhist Forms of Meditation from an Autistic Perspective. Issue 2 (November 2015) - Barber, Christopher
Abstract : The past fifty years have seen some growth in theological and spiritual interest in the sacred spaces where Christian and Buddhist spirituality and spiritual practices meet and can mutually enhance each other. Likewise, there has been an increased interest in exploring the sacred space where, in general, spirituality and disability meet. This article sets out to explore, through the eyes and spirituality of two adults with Asperger's syndrome/high functioning autism, how three specific forms of Buddhist meditative practices can be adapted to fit within a Christian spiritual paradigm